2018
DOI: 10.1101/329276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social effects of territorial neighbours on the timing of spring breeding in North American red squirrels

Abstract: Organisms can affect one another’s phenotypes when they socially interact. Indirect genetic effects occur when an individual’s phenotype is affected by genes expressed in another individual. These heritable effects can enhance or reduce adaptive potential, thereby accelerating or reversing evolutionary change. Quantifying these social effects is therefore crucial for our understanding of evolution, yet estimates of indirect genetic effects in wild animals are limited to dyadic interactions. We estimated indire… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 94 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…The genetic basis of social influence could be tested in future studies that build on our approach by using genotyping to resolve the population pedigree. This will require analytical methods that can account for genetic structure in the social environment [16,18,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic basis of social influence could be tested in future studies that build on our approach by using genotyping to resolve the population pedigree. This will require analytical methods that can account for genetic structure in the social environment [16,18,24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments have demonstrated that cooperative and social behaviours can be transmitted via social contagion and dynamic network partnerships in flies, fish, and humans [12,14,15,[21][22][23]. To date, however, these laboratory studies have considered simple dyadic or small group interactions that do not reflect realistic social complexity (but see [24]), and may overestimate social influence [8,25]. Thus, a complete understanding of social influence will require collecting repeated measures of behaviour while accounting for who interacts with whom, and the frequency with which these interactions occur in a dynamic social network.…”
Section: Introductionmentioning
confidence: 99%
“…V AD,W is generally expected to be low for populations in stable environments (for a review of estimates, see Hendry et al 2018), as directional selection is expected to erode genetic variance in fitness, while we are unaware of any estimates of cov A (D, I ), but have some expectations for how it should change with n or density (see above). We encourage empiricists to estimate these and, for example, to test whether IGEs get weaker as larger groups are considered (e.g., see the supplamentary materials of Fisher et al 2018).…”
Section: Empirical Challengesmentioning
confidence: 99%
“…The genetic basis of social influence could be tested in future studies that build on our approach by 388 using genotyping to resolve the population pedigree. This will require analytical methods that can account for genetic structure in the social environment [16,18,24]. 390…”
Section: Viewed Cumulatively Our Work Demonstrates How Multiple Sourmentioning
confidence: 99%
“…Recent experiments have demonstrated that cooperative 96 and social behaviors can be transmitted via social contagion and dynamic network partnerships in flies, fish, and humans [12,14,15,[21][22][23]. To date, however, these laboratory studies have 98 considered simple dyadic or small group interactions that do not reflect realistic social complexity [but see 24], and may overestimate social influence [8,25]. Thus, a complete 100 understanding of social influence within in a dynamic social network will require collecting repeated measures of behavior while accounting for who interacts with whom, and the frequency 102 with which these interactions occur.…”
Section: Introductionmentioning
confidence: 99%